Integration of metabolomics and transcriptomics analyses investigates the accumulation of secondary metabolites in maturing seed plumule of sacred lotus (Nelumbo nucifera). (January 2023) - He, Dongli; Rao, Xiaolan; Deng, Jiao; Damaris, Rebecca N.; Yang, Pingfang
Graphical abstract: Highlights: Integrated widely targeted metabolomics and transcriptomics study on Lotus seed plumule(LP)with different maturity. Majority of secondary metabolites greatly accumulated after 18 days after pollination (DAP), and 591 metabolites differentially accumulated in maturing LP. Transcriptomic analysis identified 11, 019 differentially expressed genes. Systematical metabolic regulation maps established for different secondary metabolites based on the comprehensive data. Abstract: Lotus seed plumule (LP) is rich in a variety of antioxidant and anti-inflammatory secondary metabolites, making it a traditional food and medicine widely used in China. Physiological and histological evidences indicated that LP mainly accumulated metabolites in 15–24 days after pollination (DAP) during their development. To systematically investigate the dynamic accumulation of major secondary metabolites, the UPLC-HRMS-based widely targeted metabolomics analyses were performed on maturing LP at 15, 18, 21, and 24 DAP. In total, 767 metabolites were identified, including many secondary metabolites, e.g., 27 % flavonoids and 8 % alkaloids. Among them, 591 were identified as differentially accumulated metabolites (DAMs). The majority of secondary metabolites showed great accumulation after 18 DAP even at the late stage of LP maturation, such as hesperidin, neohesperidin, orobol, serotonin, and lotus special O-nornuciferine, endowing mature LP with effective pharmaceutical properties. The paralleled transcriptomic analysis identified 11, 019 differentially expressed genes (DEGs). Based on the comprehensive data, several systematical metabolic regulation maps were established for different secondary metabolites, and 18 DAP was found as a switching point for LP maturing from active primary metabolism to massive secondary metabolites deposition. This study provides valuable information for understanding the mechanism of secondary metabolite accumulation in maturing LP and facilitates its pharmaceutical application.